Use of herbal products and associated factors among patients with non-communicable diseases in a rural northern Thai community: A cross-sectional study - Wuttikul, Chanadda; Tong-on, Jitsupa; Wongkeaw, Wilawan; Watcharawaleekul, Thanasak; Phattanasobhon, Sirayut (Science, Engineering and Health Studies, 2025)
This cross-sectional study investigated the prevalence of herbal product use and associated factors among patients with non-communicable diseases (NCDs) in the community of Phayao province via home visits. Data were collected from 361 patients at three sub-district health-promoting hospitals using a developed structured questionnaire. Descriptive analysis and multivariable logistic regression were established. The results showed that 61.2% of patients used herbal products, totaling 398 items, with herbal extracts being the most common (30.4%). The primary purpose was treating or relieving symptoms of illness. Factors associated with increased herbal use included age over 60 years (aOR 2.11; 95% CI 1.14–3.91), monthly income below 10,000 THB (aOR 3.47; 95% CI 1.27–9.52), former smoking status (aOR 5.78; 95%CI 1.31–25.50), use of multiple health centers (aOR 2.46; 95% CI 1.55–3.92), receiving treatment at private hospitals/clinics (aOR 6.08; 95% CI 1.15–32.07), and obtaining information about herbal products from social media (aOR 3.49; 95%CI 1.87–6.52). Herbal product use is prevalent among rural patients with NCDs in Thailand. Influencing factors include patient characteristics (older age, former smoking), socioeconomic status, healthcare utilization patterns, and information sources. Healthcare providers should be aware of these trends to ensure safe and effective patient care for NCDs in rural settings.